The STRATEGI DAN PELAKSANAAN PENDIDIKAN AKHLAK SANTRI BARU DI PONDOK PESANTREN HIDAYATUL MUBTADI’IEN KAMPAR - Agus Joko Purwanto; M. Najih (STKIP Subang, 2025)
The rapid progress of the modern era is accompanied by a decline in moral values among the younger generation. This is evident in behaviors such as disobedience to parents, drug abuse, alcohol consumption, and promiscuity, even among educated students. A lack of religious education is considered a primary factor, resulting in a fragile moral foundation for the nation’s future. This condition has encouraged many parents in the Sumatra region to enroll their children in Islamic boarding schools (pesantren). The generally firm and strong character of the local community, along with the pesantren’s mission to develop independent and morally upright individuals, makes such institutions a preferred choice. High moral character is regarded as more important than mere academic intelligence. This study aims to examine the strategies, teachers’ roles, and outcomes of moral education for new students at Pondok Pesantren Hidayatul Mubtadi’ien, Kampar, Riau. It employs a field research design with an ethnomethodological-qualitative approach. Data were collected through interviews, observations, and documentation, then analyzed through data reduction, presentation, and verification. The findings reveal that: (1) Teachers serve as role models, showing patience, perseverance, and applying effective strategies. (2) The results are positive, supported by a kitab kuning-based curriculum taught progressively from elementary to junior high levels.